Evaluation of the Foundation of the Ambon City Financial Services Authority Office Building, Maluku Based on Field Data - Chalvin Carste Talakua; Abraham Kalalimbong; Mansye R. Ayal (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to evaluate the performance of the inner foundation in the Ambon City Financial Services Authority (OJK) Office Building based on field data in the form of boring logs and Standard Penetration Test (SPT) results. The evaluation focused on axial bearing capacity, lateral resistance, and foundation degradation to assess the level of safety and reliability of the foundation system against working loads. The types of foundations analyzed included drilled pile foundations and piles with variations in diameter of 60 cm and 80 cm and depths of 18 m and 25 m. The bearing capacity analysis of the drill pile was carried out using the Reese & O'Neil and Reese & Wright methods, while the bearing capacity of the pile was calculated using the Coyle & Castello and Schmertmann methods. Lateral resistance was analyzed using the Broms method, and the estimated decline was calculated using a semi-empirical approach. The results showed that there was a difference in carrying capacity, lateral resistance, and the magnitude of the decline between the drill pile and the pile which was influenced by the size of the pile and the characteristics of the local soil. In general, the increase in the diameter and depth of the mast contributes to an increase in bearing capacity and lateral resistance and reduces the potential for degradation. These findings confirm that the selection of foundation types must consider the specific geotechnical conditions of the location in order to be able to provide optimal and safe structural performance. Keywords: drill pile foundation, pile, bearing capacity, lateral resistance, lowering, foundation evaluation.